Turasheva S.K., Boguspaev K.K., Faleev G.D., Alnurova A.A., Kapitina A.I. Restoration the population number of wild rubber endemic plant Scorzonera tau-saghyz Lipsch. et Bosse: Al-Farabi Kazakh National university, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
Scorzonera tau-saghyz Lipsch. et Bosse (tau saghyz) is rare endemicplant species of flora in Kazakhstan, which is included in the Red Book ofthe Republic of Kazakhstan. It is a strategic raw valuable species becauseit contains rubber in the root. The plant, first discovered in the KaratauMountains, grows on stony and rocky slopes, low- and middle plateaus.In nature the plant is propagated by seeds and vegetatively by stem androot grafts. Hygrophill, frost and heat-resistant mesophyte plant has a widerange of environmental spectrum, wild forms are able to accumulate inthe roots about 40% rubber. Rubber is contained in latex branches whichpenetrate roots, caudex and leaves of tau-saghyz. During the war fromnature it seized more than 14 million plants and produced 902 tons ofrubber for country’s defense industry. Restoration of its resources in a nature conditions is very slow due to the formation small amount of seeds tothe 3-4-th year of vegetation period and seedling death at a young stage.One of the problems for large-scale cultivation of tau-saghyz is a low percentage of germination and seedling growth. The reason of this issue isthe high susceptibility of seeds to various infections, impact of pests andphysiologically low energy of seed germination. The aim of this researchwas to study the different modes of stratification and priming seeds of thewild plants tau-saghyz to increase the germination and sprouting of seedsand their subsequent reproduction to restore the number of populationrare rubber plant species. It was found that the stratification of seeds at70 C for 4 weeks and treatment by 0.1% thio-urea leads to a decrease ofseeds contamination, increase the percentage of germination, as well as alarge output of healthy seedlings of endemic plants Scorzonera tau-saghyzLipsch. et Bosse.Key words: priming, propagation, Scorzonera tau-saghyz Lipsch. etBosse, stratification, tau-saghyz.